Talking hands: tongue motor excitability during observation of hand gestures associated with words - Komeilipoor, Naeem; Vicario, Carmelo Mario; Daffertshofer, Andreas; Cesari, Paola (Frontiers in Human Neuroscience, 2014)
Perception of speech and gestures engage common brain areas. Neural regions involved in speech perception overlap with those involved in speech production in an articulator-specific manner. Yet, it is unclear whether motor cortex also has a role in processing communicative actions like gesture and sign language. We asked whether the mere observation of hand gestures, paired and not paired with words, may result in changes in the excitability of the hand and tongue areas of motor cortex. Using single-pulse transcranial magnetic stimulation, we measured the motor excitability in tongue and hand areas of left primary motor cortex, while participants viewed video sequences of bimanual hand movements associated or not-associated with nouns. We found higher motor excitability in the tongue area during the presentation of meaningful gestures (noun-associated) as opposed to meaningless ones, while the excitability of hand motor area was not differentially affected by gesture observation. Our results let us argue that the observation of gestures associated with a word results in activation of articulatory motor network accompanying speech production.